SME banking of IFIC bank limited: a comparative study among City bank, Eastern bank and IFIC bank - Afrin, Sifat (BRAC University, 2012)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2011.